A flexible electric actuator based on sprayed non-metallic electrode and its preparation method
The manufacturing complex in the prior art is solved by using an ionic polymer intermediate layer made of thermoplastic polyurethane elastomer and ionic liquid in a flexible electrical actuator, combining ultrasonic spraying of non-metal conductive polymer materials and carbon nanotubes to form an electrode layer. The high-performance and cost problems achieve efficient and stable preparation of flexible electrical actuators and custom patterning.
Patent Information
- Application Number
- CN202210097325.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-01-27
AI Technical Summary
The existing flexible electrical actuators are complex and costly in the manufacturing process of the electrode layer. The difference in the mechanical properties of the metal electrode materials and the intermediate layer of the ion polymer leads to the impact of driving reliability, making it difficult to achieve large-scale manufacturing and custom patterns. change.
Thermoplastic polyurethane elastomer (TPU) particles are mixed with ionic liquid to form an ionic polymer intermediate layer, and the electrode composed of PEDOT:PSS and carbon nanotubes is sprayed through ultrasonic spraying equipment and XY two-axis mobile device. layer, flexible electrical actuator forming a sandwich structure.
It achieves a displacement of about 2mm within a few seconds under ±3V DC voltage and returns to the initial position after power outage. The performance is comparable to that of the metal electrode layer. The process is simple, fast and stable, and is suitable for large-scale patterning manufacturing.
Smart Images

Figure CN114497346B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible electric actuator based on spraying non-metallic electrodes and a preparation method thereof, and belongs to the field of flexible electronic devices. Background Art
[0002] With the continuous evolution of human-interactive flexible electronic devices, flexible tactile sensing systems including tactile biopsychological systems, tactile rendering systems and touch interfaces have gradually attracted the attention of researchers. "Artificial muscles" that act as effectors are an important part of flexible tactile sensing systems, which is a field that overlaps multiple disciplines such as materials science, chemical engineering, mechanical engineering, electrical engineering and chemistry. As a general term for a class of materials and devices, artificial muscle devices can reversibly contract, expand or rotate within a component due to various external stimuli (such as voltage, current, pressure, temperature, light intensity, etc.), thereby achieving various actuation effects.
[0003] In particular, in flexible electronic systems, in order to connect the artificial muscle "effector" and the front-end "receptor" (sensing module), artificial muscles actuated by electrical signals, namely flexible electric actuators, have a wide range of applications. Compared with rigid devices, flexible electric actuators are elastic and can provide better protection for clamped objects (especially fragile objects) when used as robot hands. At the same time, their flexible properties can also help them flexibly adapt to changing environments, and their unlimited cutting properties also make them widely used in microsystems. If multiple functions such as drug delivery, multi-mode sensing, biocompatibility and biodegradability, and color change are integrated into the device, flexible electric actuators will play a significant role in many fields such as aerospace, biomedical engineering, military, space exploration, and deep-sea exploration.
[0004] Flexible electric actuators usually include two parts: a polymer middle layer and an electrode layer. According to the type of polymer, there are two types: conductive polymer type and ionic polymer type. Conductive polymer type flexible electric actuators are driven by electric fields. Compared with ionic polymer type flexible electric actuators, they require a very high voltage to be applied, so they are usually not used in human body interactive flexible electronic systems. Ionic polymer type flexible electric actuators can cause the ions in the polymer middle layer to move to the two poles by applying a small DC voltage at both ends of the electrode layer. The size difference between anions and cations further causes the device to produce reversible bending corresponding to the voltage polarity. However, for the electrode layer of flexible electric actuators, existing research usually uses the method of evaporating precious metals (such as gold, platinum, etc.) or physical vapor deposition of indium tin oxide (ITO) thin films. The former is complex and expensive, and is limited by the vacuum requirements of micro-machining process equipment, so it cannot be manufactured on a large scale; the latter is prone to cracking during the operation of the device due to the brittle properties of similar films such as ITO, thereby affecting the cycle life of the device.
[0005] In order for flexible electric actuators to have a faster response speed when used in scenarios such as robot hands, the device needs to have an appropriate size, the electrode layer needs to have good conductivity, the ions in the ionic polymer layer need to have good mobility, and the components of the ionic polymer layer and the electrode layer need to have good mechanical properties. Metal materials such as Pt can have extremely strong conductivity when used as electrode materials, but they are expensive, and large-scale manufacturing is hindered by related micro-processing equipment. At the same time, due to the huge difference in mechanical properties between the metal and ionic polymer intermediate layers, the driving reliability of the device will be greatly affected. Therefore, it is of great significance to use non-metallic materials as electrode layers. Not only can large-scale preparation and customized patterning be carried out at low cost and convenience, but the actuation speed (bandwidth) of the device will also be better guaranteed. Summary of the invention
[0006] The purpose of the present invention is to provide a flexible electric actuator based on spraying non-metallic electrodes and a preparation method thereof in view of the problems in the prior art. The present invention adopts thermoplastic polyurethane elastomer (TPU) particles and ionic liquid 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ([EMIM]+[TFSI]-) to mix and prepare an ionic polymer intermediate layer.
[0007] Ultrasonic spraying equipment and XY two-axis moving device are used to spray non-metallic conductive polymer materials PEDOT:PSS and carbon nanotubes (CNT) and electrode layers composed of related additives on both sides. The prepared flexible electric actuator can produce a displacement of about 2mm in the corresponding direction within a few seconds under a DC voltage of ±3V, and return to the initial position after power failure. The performance of the prepared flexible electric actuator is comparable to that of the flexible electric actuator using a metal electrode layer, but the process is simple, the preparation is fast, the stability is good, and large-scale patterning can be achieved.
[0008] The present invention adopts the following technical solutions to solve the above technical problems:
[0009] A flexible electric actuator based on sprayed non-metallic electrodes, the flexible electric actuator is a sandwich structure, including an ionic polymer middle layer and non-metallic electrode layers on its upper and lower sides;
[0010] The ion polymer intermediate layer is made of a mixture of polyurethane elastomer particles and ionic liquid;
[0011] The non-metal electrode layer is composed of non-metal conductive polymer material, carbon nanotubes and additives.
[0012] Furthermore, the additives are DMSO, ethanol and ionic liquid; the non-metallic conductive polymer material is PEDOT:PSS; and the ionic liquid is 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ([EMIM]+[TFSI]-).
[0013] Furthermore, the thickness of the ionic polymer intermediate layer is 0.2-0.4 mm; the thickness of the non-metallic electrode layer is 1-5 μm.
[0014] A method for preparing a flexible electric actuator based on spraying non-metallic electrodes comprises the following steps:
[0015] S1, preparing an i-TPU ionomer intermediate layer;
[0016] S2, preparing a non-metallic electrode precursor solution;
[0017] S3, attaching the electrode layer precursor solution prepared in step S2 to the upper and lower surfaces of the ionic polymer intermediate layer prepared in step S1 through an ultrasonic spraying process, thereby preparing the flexible electric actuator.
[0018] A method for preparing a flexible electric actuator based on spraying a non-metallic electrode, characterized in that step S1 comprises the following steps:
[0019] S11. Heat the N,N-dimethylformamide solution in a flask to 80°C, slowly add the TPU particles, and stir until all dissolved;
[0020] S12, adding ionic liquid to the flask in step S11, and magnetically stirring at 80° C. for 12 hours to obtain an i-TPU solution;
[0021] S13, placing the i-TPU solution obtained in step S12 in a 60° C. oven and letting it stand for 2 hours to remove bubbles on the upper layer, then dropping it on the middle of the glass culture dish cover while it is still hot and placing it on a horizontal optical platform and letting it stand for 5 minutes to allow the i-TPU solution to be evenly dispersed; the ratio between the diameter of the culture dish cover and the mass of the dropped i-TPU solution is 3 cm:2 g;
[0022] S14, placing the culture dish cover of step S13 into a 40°C oven, increasing the temperature by 10°C every hour until the temperature in the oven reaches 120°C, maintaining this temperature for 24 hours, and then evacuating the oven for 12 hours; after cooling, using tweezers to peel off the i-TPU ionomer intermediate layer from the culture dish cover to obtain the i-TPU ionomer intermediate layer.
[0023] Furthermore, the mass ratio of the added N,N-dimethylformamide solution, TPU particles and ionic liquid is 3:1:1.2.
[0024] Further, step S2 includes the following steps:
[0025] S21, take PEDOT:PSS aqueous dispersion solution, add DMSO, ethanol and ionic liquid, and stir in a water bath at 40°C for 3 hours;
[0026] S22, slowly adding carbon nanotubes into the mixed solution that is being magnetically stirred in step S21, continuing stirring for 1 hour, and then subjecting the mixed solution to ultrasonic treatment at 90W for 3 minutes to uniformly disperse the carbon nanotubes, thereby obtaining the non-metallic electrode precursor solution.
[0027] Furthermore, the mass ratio of the PEDOT:PSS aqueous dispersion solution, DMSO, ethanol, ionic liquid and carbon nanotubes is 300:15:35:4.5:1.3.
[0028] Further, step S3 includes the following steps:
[0029] S31, use a 5mL syringe to absorb the non-metallic electrode precursor solution and place it on the propulsion pump, set the propulsion speed to 0.8mL / min, and exhaust the air in the liquid inlet hose after running for a period of time. At the same time, turn on the hot stage, set the temperature to 80°C, and open the compressed nitrogen valve connected to the ultrasonic nozzle, with an air pressure of 0.1MPa;
[0030] S32, connecting the ultrasonic nozzle to the XY two-axis moving device, so that the nozzle moves in an "S-shaped" path for subsequent uniform spraying, the moving speed is set to 5 mm / s, the distance between the bottom of the ultrasonic nozzle and the hot stage is 25 cm, and the i-TPU ion polymer intermediate layer prepared in step S1 is placed in the center of the hot stage for preheating;
[0031] S33, first turn on the ultrasonic generator switch of the ultrasonic nozzle, control the frequency within 60.2kHz-60.8kHz, then start the propulsion pump liquid feeding program, and spray at a propulsion speed of 0.8mL / min for 10 minutes;
[0032] S34, placing the i-TPU ionomer intermediate layer sprayed with a single-sided non-metallic electrode layer on a glass slide, and placing it in a tube furnace for high-temperature annealing;
[0033] S35, repeating steps S33 and S34 on the side of the i-TPU ionic polymer intermediate layer that is not sprayed with the non-metallic electrode layer to obtain an ionic polymer intermediate layer sprayed with double-sided non-metallic electrode layers, i.e., the flexible electric actuator based on spraying non-metallic electrodes.
[0034] Furthermore, the annealing procedure in step S34 is: heating from 25° C. to 160° C. within 15 minutes and maintaining for 1 hour, followed by natural cooling.
[0035] Device principle: The ionic polymer middle layer and the non-metallic electrode layers sprayed on its upper and lower surfaces constitute a double electrode layer (EDL) structure. When a small DC voltage is applied to the electrodes on both sides, a small electric field is formed in the ionic polymer middle layer, and the cations and anions in it move to the vicinity of the corresponding electrode layer surface under the action of the electric field. Due to the difference in the volume size of cations and anions, the mechanical bending of the entire flexible electric actuator will be triggered when a certain number of them are gathered.
[0036] Beneficial Effects
[0037] The preparation method of the present invention can not only be conveniently and cost-effectively carried out in large-scale preparation and customized patterning, but also the actuation speed (bandwidth) of the device can be better guaranteed. The flexible electric actuator prepared by the present invention can produce a displacement of about 2mm in the corresponding direction within a few seconds under a DC voltage of ±3V, and return to the initial position after power failure.
[0038] As a classic non-metallic electrode material, PEDOT:PSS has good conductivity, excellent mechanical properties and better dispersion in aqueous solution than other non-metallic electrode materials. However, since the PEDOT:PSS aqueous dispersion does not contact the hydrophobic surface of the ionic polymer interlayer (i-TPU) very well, some specific substances are needed to optimize the contact between the PEDOT:PSS electrode and the ionic polymer interlayer.
[0039] The addition of DMSO can improve the molecular arrangement of PEDOT:PSS, making it more orderly, thus forming a channel with higher conductivity. At the same time, DMSO can optimize the surface contact between the PEDOT:PSS non-metallic electrode layer and the ionic polymer intermediate layer (i-TPU), so that the PEDOT:PSS chain can better blend with i-TPU. In fact, in the comparative test, it can be seen that the DMSO-doped PEDOT:PSS aqueous dispersion has a smaller contact angle on the hydrophobic surface of i-TPU than the pure PEDOT:PSS aqueous dispersion.
[0040] Diluting the PEDOT:PSS aqueous dispersion with ethanol to a certain proportion can greatly improve the conductivity and flatness of the sprayed PEDOT:PSS electrode layer. First, ethanol, as an organic solvent, can increase the viscosity of the PEDOT:PSS aqueous dispersion by doping it into PEDOT:PSS, thereby reducing the surface tension of the liquid and improving the contact between the droplet and the substrate; secondly, the original PEDOT:PSS aqueous dispersion is prone to agglomeration during film formation, and dilution with ethanol can promote the phase separation of PEDOT and PSS, making the agglomerated PEDOT:PSS particles on the final electrode layer smaller or even disappear, and the surface of the electrode film smoother; in addition, the organic solvent ethanol can also change the configuration of the PEDOT polymer chain in the PEDOT:PSS aqueous dispersion from a curled type to a linear or expanded curled type, thereby improving the conductivity of the non-metallic electrode layer.
[0041] Adding a certain amount of carbon nanotubes (CNTs) to the DMSO-doped ethanol-diluted PEDOT:PSS solution and performing ultrasonic treatment to make it evenly distributed in the aqueous dispersion can further improve the conductivity of the non-metallic electrode layer and its adhesion to the ionic polymer intermediate layer. In the early stage of ultrasonic spraying, thanks to the huge aspect ratio of CNTs, CNTs fall on the surface of the ionic polymer intermediate layer (i-TPU) and act as a bridge, which to some extent offsets the negative effect of the i-TPU hydrophobic surface on the adhesion of the electrode material. With the progress of ultrasonic spraying and the initial attachment of PEDOT:PSS, CNTs are interconnected with each other and with PEDOT and PSS, further improving the conductivity of the non-metallic electrode layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The basic structure and function diagram of the flexible electric actuator manufactured by the present invention;
[0043] Figure 2 Schematic diagram of the microstructures of the ionic polymer intermediate layer and the non-metallic electrode layer of the flexible electric actuator prepared by the present invention;
[0044] Figure 3 The moving track design diagram of the ultrasonic nozzle with XY two-axis moving device used in the present invention;
[0045] Figure 4 The figure is a physical picture of the flexible electric actuator made by the present invention and a schematic diagram of its displacement when a +3V DC voltage is applied;
[0046] Figure 5 A scanning electron microscope (SEM) image of the non-metallic electrode layer sprayed on the flexible electric actuator prepared by the present invention;
[0047] Figure 6The figure is a displacement-time curve diagram of the flexible electric actuator manufactured by the present invention measured by a laser ranging device. DETAILED DESCRIPTION
[0048] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention.
[0049] Example 1: The ionic polymer intermediate layer of the flexible electric actuator is prepared as follows:
[0050] 1. Use a balance to weigh 10g of TPU pellets and place them in a petri dish for later use. At the same time, use a pipette to take 30g of N,N-dimethylformamide (DMF) solution (the volume is 31.75mL according to the density of DMF at this temperature) into a round-bottom flask and place it in a water bath and heat it to 80°C;
[0051] 2. Add a magnetic stirrer to the round-bottom flask for stirring, and slowly add TPU particles (adding too fast will easily cause the semi-dissolved TPU particles to accumulate at the bottom of the flask, hindering stirring), and stir for about 1 hour until the TPU particles are completely dissolved in DMF;
[0052] 3. Add 120% (i.e. 12 g) of ionic liquid 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide ([EMIM]) to the round-bottom flask. + [TFSI] - ), and magnetically stirred at 80°C for 12 h;
[0053] 4. The i-TPU solution prepared by the above steps was placed in a 60°C oven for 2 hours to remove the upper bubbles, and then dripped on the middle of the special glass culture dish cover while hot (the diameter of the culture dish cover is 6 cm, and the mass of the i-TPU solution dropped is 4.0 g) and placed on a horizontal optical platform for 5 minutes to allow the i-TPU solution to be evenly dispersed;
[0054] 5. Place the glass culture dish cover coated with i-TPU solution in a 40°C oven (no vacuum is required), increase the temperature by 10°C every hour until the temperature in the oven reaches 120°C, maintain this temperature for 24 hours, and then vacuum the oven for 12 hours to exhaust the toxic gases and water vapor in the oven;
[0055] 6. Turn off the oven heating system, wait for the glass culture dish cover to cool down, and then use tweezers to peel off the i-TPU ion polymer middle layer from the culture dish cover.
[0056] Example 2: The ultrasonic spraying non-metallic electrode layer of the flexible electric actuator is prepared as follows:
[0057] 1. Take 30g PEDOT:PSS aqueous dispersion solution, add 1.5g DMSO, 3.5g ethanol and 0.45g ionic liquid, and stir in a 40℃ water bath for 3 hours;
[0058] 2. Weigh 0.13 g of carbon nanotubes (CNT) on a weighing paper with a balance and add the CNT to the mixed solution under magnetic stirring with a small spoon. Continue stirring for 1 hour and then perform ultrasonic treatment at 90 W for 3 minutes to evenly disperse the CNT to obtain a non-metallic electrode precursor solution.
[0059] 3. Use a 5mL syringe to absorb the non-metallic electrode precursor solution and place it on the propulsion pump. Set the propulsion speed to 0.8mL / min. After running for a period of time, exhaust the air in the liquid inlet hose. At the same time, turn on the hot stage (set the temperature to 80℃) and open the compressed nitrogen valve connected to the ultrasonic nozzle (air pressure 0.1MPa);
[0060] 4. Connect the ultrasonic nozzle to the XY two-axis moving device so that the nozzle moves in an "S-shaped" path (see attached Figure 3 ) Circular movement for subsequent uniform spraying, the moving speed is set to 5 mm / s, the distance between the bottom of the ultrasonic nozzle and the hot stage is 25 cm, and the pre-prepared i-TPU ion polymer intermediate layer is placed in the center of the hot stage for preheating;
[0061] 5. First turn on the ultrasonic generator switch of the ultrasonic nozzle, control the frequency within 60.2kHz-60.8kHz, then start the propulsion pump liquid feeding program, and spray at a propulsion speed of 0.8mL / min for 10 minutes;
[0062] 6. Place the i-TPU sprayed with a single-sided non-metallic electrode layer on a glass slide and put it into a tube furnace for high-temperature annealing (annealing procedure: heating from 25°C to 160°C within 15 minutes and maintaining for 1 hour, followed by natural cooling);
[0063] 7. Repeat steps 5 and 6 on the side of the i-TPU that is not sprayed with the non-metallic electrode layer to obtain an ionic polymer intermediate layer sprayed with double-sided non-metallic electrode layers, that is, a flexible electric actuator based on sprayed non-metallic electrodes.
Claims
1. A flexible electric actuator based on sprayed non-metallic electrodes, characterized in that: The flexible electric actuator is a sandwich structure, including an ionic polymer middle layer and non-metallic electrode layers on its upper and lower sides; The ion polymer middle layer is made of polyurethane elastomer particles and ionic liquid to form an i-TPU ion polymer middle layer; The non-metallic electrode layer is composed of non-metallic conductive polymer materials, carbon nanotubes and additives; The additives are DMSO, ethanol and ionic liquid; the non-metallic conductive polymer material is PEDOT:PSS; and the ionic liquid is 1-ethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide.
2. A flexible electric actuator based on sprayed non-metallic electrodes as claimed in claim 1, characterized in that: The thickness of the ionic polymer intermediate layer is 0.2-0.4 mm; the thickness of the non-metallic electrode layer is 1-5 μm.
3. A method for preparing a flexible electric actuator based on spraying non-metallic electrodes as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1, preparing an i-TPU ionomer intermediate layer; S2, preparing a non-metallic electrode precursor solution; S3, attaching the electrode layer precursor solution prepared in step S2 to the upper and lower surfaces of the ionic polymer intermediate layer prepared in step S1 through an ultrasonic spraying process, thereby preparing the flexible electric actuator.
4. A method for preparing a flexible electric actuator based on spraying non-metallic electrodes as claimed in claim 3, characterized in that: Step S1 includes the following steps: S11, heat the N,N-dimethylformamide solution in a flask to 80 °C, slowly add TPU particles, and stir until all dissolved; S12, adding ionic liquid to the flask in step S11, and magnetically stirring at 80° C. for 12 hours to obtain an i-TPU solution; S13, placing the i-TPU solution obtained in step S12 in a 60°C oven and letting it stand for 2 hours to remove the upper bubbles, then dropping it on the middle of the glass culture dish cover while it is still hot and placing it on a horizontal optical platform and letting it stand for 5 minutes to allow the i-TPU solution to be evenly dispersed; the ratio between the diameter of the culture dish cover and the mass of the dropped i-TPU solution is 3 cm:2 g; S14, placing the culture dish cover of step S13 into a 40°C oven, increasing the temperature by 10°C every hour until the temperature in the oven reaches 120°C, maintaining this temperature for 24 hours, and then evacuating the oven for 12 hours; after cooling, using tweezers to peel off the i-TPU ionomer intermediate layer from the culture dish cover to obtain the i-TPU ionomer intermediate layer.
5. A method for preparing a flexible electric actuator based on spraying non-metallic electrodes as claimed in claim 4, characterized in that: The mass ratio of the added N,N-dimethylformamide solution, TPU particles and ionic liquid is 3:1:1.
2.
6. A method for preparing a flexible electric actuator based on spraying non-metallic electrodes as claimed in claim 3, characterized in that: Step S2 includes the following steps: S21, taking a PEDOT:PSS aqueous dispersion solution, adding DMSO, ethanol and ionic liquid, and stirring in a water bath at 40°C for 3 hours; S22, slowly adding carbon nanotubes into the mixed solution that is being magnetically stirred in step S21, continuing stirring for 1 hour, and then subjecting the mixed solution to ultrasonic treatment at 90W for 3 minutes to uniformly disperse the carbon nanotubes, thereby obtaining the non-metallic electrode precursor solution.
7. A method for preparing a flexible electric actuator based on spraying non-metallic electrodes as claimed in claim 6, characterized in that: The mass ratio of the PEDOT:PSS aqueous dispersion solution, DMSO, ethanol, ionic liquid and carbon nanotubes is 300:15:35:4.5:1.
3.
8. A method for preparing a flexible electric actuator based on spraying non-metallic electrodes as claimed in claim 3, characterized in that: Step S3 includes the following steps: S31, use a 5mL syringe to draw the non-metallic electrode precursor solution and place it on the propulsion pump, set the propulsion speed to 0.8mL / min, and exhaust the air in the liquid inlet hose after running for a period of time. At the same time, turn on the hot stage, set the temperature to 80 °C, and open the compressed nitrogen valve connected to the ultrasonic nozzle, with an air pressure of 0.1MPa; S32, connecting the ultrasonic nozzle to the XY two-axis moving device, so that the nozzle moves in an "S-shaped" path for subsequent uniform spraying, the moving speed is set to 5 mm / s, the distance between the bottom of the ultrasonic nozzle and the hot stage is 25 cm, and the i-TPU ion polymer intermediate layer prepared in step S1 is placed in the center of the hot stage for preheating; S33, first turn on the ultrasonic generator switch of the ultrasonic nozzle, control the frequency within 60.2kHz-60.8kHz, then start the propulsion pump liquid feeding program, and spray at a propulsion speed of 0.8mL / min for 10 minutes; S34, placing the i-TPU ionomer intermediate layer sprayed with a single-sided non-metallic electrode layer on a glass slide, and placing it in a tube furnace for high-temperature annealing; S35, repeating steps S33 and S34 on the side of the i-TPU ionic polymer intermediate layer that is not sprayed with the non-metallic electrode layer to obtain an ionic polymer intermediate layer sprayed with double-sided non-metallic electrode layers, i.e., the flexible electric actuator based on spraying non-metallic electrodes.
9. A method for preparing a flexible electric actuator based on spraying non-metallic electrodes as claimed in claim 8, characterized in that: The annealing procedure in step S34 is: heating from 25 °C to 160 °C within 15 minutes and maintaining for 1 hour, followed by natural cooling.
Citation Information
Patent Citations
Novel composition for conductive transparent film
CN103228729A
Electrochemical driver using nitrogen-rich porous carbon as electrode and preparation method of electrochemical driver
CN110415857A